EFFECT OF ESSENTIAL OIL OF Cestrum nocturnum FLOWERS CULTIVATED IN IRAQ AS ANTIOXIDANT AND ELONGATION COLD STORAGE PERIOD OF MINCED MEAT - & et al., Salman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this study is extraction, estimation and identification of volatile oil in flowers Cestrum nocturnum plant, and study the antioxidant effect of oil it’s effect  on the chemical properties of minced cattle meat which was stored on fridge to elongation period of cold storage. Steam distillation method was used to extraction volatile oil and gaze  chromatography-Mass (GC-Mass) to estimate quantitative and qualitative active compounds in oil, Using diphenyl-2-picryl-hydrazyl(DPPH) and ascorbic acid as a positive comparison was determined the antioxidant effect. Some chemical testes was done on minced cattle meat by used 200mg\ml from oil under 4˚c for (0,3,7 and 10).The results showed that volatile oil containing 39 compounds but  oleic acid is more than other compounds (24,49%),then the oil has antioxidant effect 100% at 100µl\ml. The results of oil effect on minced cattle meat was showed decreased on thiobarbituric acid(TBA) and total   violate nitrogen (TVN) under 4˚c after 15 day, but the pH value was not changed. The volatile oil of Cestrum nocturnum flowers had antioxidant activity and mixing of  this oil with minced cattle meat led to increase of period of save to 15 day .